1993
DOI: 10.1590/s0034-89101993000400002
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo de eficácia de larvitrampas e ovitrampas para vigilância de vetores de dengue e febre amarela

Abstract: Com a finalidade de aprimorar a vigilância entomológica dos vetores de Dengue e Febre Amarela - Aedes aegypti e Aedes albopictus - no Estado de São Paulo, Brasil, realizou-se estudo comparativo de eficácia de larvitrampas (armadilhas de larvas), e ovitrampas (armadilhas de ovos). A região estudada é infestada somente pelo Aedes albopictus, espécie que conserva hábitos silvestres, mas também coloniza criadouros artificiais. A primeira parte do estudo foi realizada em área periurbana de Tremembé-SP, onde foram c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
2
9

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 4 publications
0
11
2
9
Order By: Relevance
“…However, such a trap has many disadvantages such as low sensitivity and the eggs laid in the trap have to be in contact with water for hatching. In Brazil, the tyre-section larval trap was evaluated in the field and the results showed that ovitraps are much more sensitive than larval traps (Marques et al 1993). In spite of the difference in sensitivity, larval traps are still widely used in Ae.…”
Section: Larval Trapsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, such a trap has many disadvantages such as low sensitivity and the eggs laid in the trap have to be in contact with water for hatching. In Brazil, the tyre-section larval trap was evaluated in the field and the results showed that ovitraps are much more sensitive than larval traps (Marques et al 1993). In spite of the difference in sensitivity, larval traps are still widely used in Ae.…”
Section: Larval Trapsmentioning
confidence: 99%
“…aegypti larvae) is considered the most effective way of reducing and controlling the mosquito populations (Gubler 1998 In subtropical countries such as Brazil, mosquito population density, dengue transmission, and the number of DF cases start to increase at the beginning of the rainy season (October), with dengue cases peaking more than three months later (Coutinho et al 2006, Forattini et al 1995. In Brazil, dengue fever re-emerged as a major urban epidemic in 1986 (Marques et al 1993) and currently is considered the most important arthropod-borne viral disease (MS 2007a,b Transmission of dengue depends on a variety of variables in the relation between virus, mosquito vector and human host (Focks et al 1995, Kuno 1997. In the assessment of dengue risk, important factors are the level of herd immunity in the human population and the ratio of mosquito to human density, which influences the probability of vector-host contacts.…”
Section: Introductionmentioning
confidence: 99%
“…Nesta área, utilizando a mesma metodologia empregada por Marques 6 , 1993, foram distribuídas 48 ovitrampas, dispostas em 12 quadras, sendo instaladas 4 ovitrampas em cada quadra, colocadas no peridomicílio de residências próximas às esquinas para possibilitar uma área de abrangência maior, com relação à sua atratividade (Figura 1). As ovitrampas consistiam de vidros pretos com abertura de 5cm de diâmetro por 12cm de profundidade, nos quais foram instaladas paletas de eucatex de 12cm de comprimento por 2cm de largura, presas por prendedores de madeira à borda do recipiente e mergulhadas em 200ml de água de abastecimento.…”
Section: Methodsunclassified
“…com intervalo de 7 dias a cada ciclo; . nebulização domiciliar (casa/casa), com emprego de máquinas costais tipo Breteau 1 e ovitrampas 6 , visando identificar a sensibilidade desses 2 métodos para detectar o reaparecimento dos vetores.…”
unclassified
“…Por outro lado, se os programas de controle não levam em conta a A restrita tendência para emprego de novos índices precisa ser alterada, com estudos e novas abordagens. Marques e colaboradores 21 , por exemplo, comprovaram maior eficiência da ovitrampa, em relação a larvitrampa, mas somente a última armadilha continua sendo amplamente empregada. Adicionalmente, outros índices sequer são mencionados em manuais de operação de controle de vetores.…”
Section: Significado Epidemiológicounclassified